2019
DOI: 10.2147/dmso.s223880
|View full text |Cite
|
Sign up to set email alerts
|

<p>Aortic Stiffness Index And Carotid Intima-Media Thickness Are Independently Associated With The Presence Of Microalbuminuria In Patients With Type 2 Diabetes Mellitus</p>

Abstract: PurposeMicroalbuminuria is a premature and widely used indicator of diabetic nephropathy and is reported to be related with a higher cardiovascular risk in diabetic patients. We aimed to examine whether the echocardiographic parameters, such as epicardial fat thickness (EFT), carotid intima-media thickness (CIMT) and aortic stiffness index (ASI) are associated with microalbuminuria in patients with diabetes mellitus type 2 (T2DM).Patients and methodsA total of 272 consecutive patients were enrolled and after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…A CIMT ≥1 mm was significantly associated with the presence of microalbuminuria and independently predicted an unfavorable early functional outcome in ischemic stroke patients, increasing the risk by 19.14 fold. These findings support prior research demonstrating a strong correlation between increased CIMT and the risk of adverse stroke outcomes [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 90%
“…A CIMT ≥1 mm was significantly associated with the presence of microalbuminuria and independently predicted an unfavorable early functional outcome in ischemic stroke patients, increasing the risk by 19.14 fold. These findings support prior research demonstrating a strong correlation between increased CIMT and the risk of adverse stroke outcomes [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 90%
“…Similar results for EFT, cIMT and presence of carotid plaque were reported by others (48). Furthermore, compared with a T2DM normoalbuminuric group, EFT and cIMT were significantly higher in those with T2DM and microalbuminuria (P<0.05 for all) (49). In logistic regression analysis, cIMT (OR 3.15, 95% CI: 1.5-36.3, P=0.024) was independently related to the presence of microalbuminuria in these patients (49).…”
Section: Epicardial Fat Thickness (Eft)mentioning
confidence: 87%
“…A previous study showed that CIMT was higher in hemodialysis subjects when compared with controls [ 24 ]. CIMT is independently associated with microalbuminuria in type 2 DM patients [ 33 ]. Patel et al investigated CIMT in 62 CKD patients and 50 controls.…”
Section: Discussionmentioning
confidence: 99%